In praise of the few: studies in Shiʻi thought and history - Kohlberg, Etan (Shii Islam: texts and studies, 2020)
"In Praise of the Few: Studies in Shiʻi Thought and History is a selection of Etan Kohlberg's research on Shiʻi Islam over a period of fifty years. It includes previously published articles, revised dissertation chapters, and a full bibliography of the author's work. Divided into two parts, the collection begins with chapters from Kohlberg's Oxford doctoral dissertation (1971) and related articles that investigate Sunni and Shiʻi views on the Prophet's Companions and debates concerning the extent of their authority as sources of religious knowledge. Part Two traces the doctrinal and historical developments pertaining to various dimensions of Imāmī Shiʻi intellectual tradition such as theology, hadith, law and jurisprudence. and exegesis"--